Bis[N `-(2-oxo-1H-indol-3-ylidene)thiophene-2-carbohydrazidato-kappa O-3,N `,O `]zinc(II) N,N-dimethylformide monosolvate monohydrate - Halim, S.N.A.; Ali, H.M.; Ng, S.W. (International Union of Crystallography, 2010)
The metal atom of the title compound, [Zn(C13H8N3O2S)(2)]center dot C3H7NO center dot H2O, is O,N,O `- chelated by two deprotonated Schiff bases and it exists in a distorted octahedral geometry. The N-H groups of the ligands, the carbonyl group of the DMF molecule and uncoordinated water molecule engage in N-H center dot center dot center dot O and O-H center dot center dot center dot O interactions, generating a hydrogen-bonded ribbon that propagates along [110]. One thienyl ring is disordered over two positions in a 1:1 ratio.